MINAT KERJA DI PERUSAHAAN BERORIENTASI LINGKUNGAN: PERAN PEMAHAMAN GREEN ACCOUNTING, NILAI SOSIAL, DAN LOCUS OF CONTROL - Angraeni, Viska; Sahrir; Sofyan Syamsuddin (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to examine the effect of accounting students' understanding of green accounting, social values, and locus of control on their interest in pursuing careers in environmentally oriented companies. A quantitative approach was employed, utilizing a saturated sampling technique with data collected from 70 final-year accounting students at the University of Muhammadiyah Palopo through an online questionnaire using a Likert scale and analyzed with IBM SPSS version 30.0. The findings revealed that students' understanding of green accounting positively and significantly influences their interest in working in environmentally oriented companies, reflecting an increasing awareness of sustainability within the accounting profession. Social values, however, did not show a significant effect, suggesting that students prioritize pragmatic factors such as career prospects over social considerations. Conversely, locus of control demonstrated a positive and significant effect, indicating that students with a stronger internal locus of control are more inclined to pursue sustainability-driven careers. These findings highlight the need for integrating green accounting into the curriculum to enhance students’ understanding and interest in sustainability. Additionally, organizations can foster internal locus of control through tailored recruitment and professional development strategies. This study offers novel insights into the interplay of green accounting, social values, and locus of control in shaping career interests, addressing an underexplored area in accounting education